Electronic and optical properties of orthorhombic (CH 3 NH 3 )BX 3 (B = Sn, Pb; X = F, Cl, Br, I) perovskites: a first-principles investigation - Nations, Sean; Jia, Ting; Wang, Shengnian; Duan, Yuhua (RSC advances, 2021)
Lead halide perovskites have generated considerable interest in solar cell, sensor, and electronics applications. While great focus has been placed on (CH 3 NH 3 )PbI 3 , an organic–inorganic hybrid perovskite, comparatively little work has been done to understand some of its existing crystal phases and analogous materials after substituting with Sn and/or other halogens in the framework. Here, first-principles density functional theory calculations are performed to comprehensively evaluate the electronic and optical properties of (CH 3 NH 3 )BX 3 (B = Sn, Pb; X = F, Cl, Br, I) in a low-temperature orthorhombic phase. Bulk modulus, electronic structures, and several optical properties of these perovskite systems are further calculated. The obtained results are first confirmed by comparing with existing perovskite systems in literature. The shifting trends on those physical properties when extending to other barely studied systems of (CH 3 NH 3 )BX 3 is further revealed. The band gap of these perovskites is found to decrease when varying halogen anion in “X” sites from F to I, and/or substituting Pb cations with Sn in “B” sites. Notably, the less toxic Sn-containing perovskites, (CH 3 NH 3 )SnI 3 in particular, display higher absorption coefficients in the visible light range than their Pb-containing counterparts. An orthorhombic (CH 3 NH 3 )PbF 3 is predicted to exist at low temperature, and adsorb strongly UV energy. Our systematical examination efforts on the two groups of perovskites provide valuable physical insights in these materials, and the accompanied new findings warrant further investigation on such subjects.